A ceramic-based sweating cooling medium material for in-situ implantation of thermocouples and a preparation method thereof

By implanting thermocouples in situ in ceramic-based sweat cooling medium materials, combined with the use of alumina powder, mullite fibers and carbon fibers, the problem of poor cooling effect of existing materials and inability to achieve real-time temperature feedback is solved, and efficient intelligent sweat cooling effect is achieved, meeting the thermal protection needs of hypersonic aircraft.

CN118439876BActive Publication Date: 2025-04-01BEIJING JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410644710.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-04-01
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

The existing sweat cooling materials have poor cooling effect and cannot achieve real-time temperature feedback function, resulting in the intelligent sweat cooling system being unable to effectively control the amount of sweating and unable to meet the thermal protection needs of hypersonic aircraft.

Method used

Alumina powder and mullite fiber are used as raw materials, carbon fiber is the pore-forming agent, and thermocouple wire is the implanted test element. Connected pores are formed through overlap between fibers and particles and oxidation of pore-forming agent. Combined with grinding and molding technology, the uniformity and mechanical strength of the pore structure are improved, and the in-situ implantation thermocouple design is implemented to achieve real-time monitoring and feedback of the internal temperature of the material.

Benefits of technology

The prepared ceramic-based sweat cooling medium material has the characteristics of low density, high temperature resistance, and uniform pore structure communication. The water permeability and compressive strength are improved, which can effectively realize the real-time control of the intelligent sweat cooling system and meet the thermal protection needs of hypersonic aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118439876B_ABST
    Figure CN118439876B_ABST
Patent Text Reader

Abstract

The present invention discloses a ceramic-based sweating cooling medium material for in-situ implantation of thermocouples and a preparation method thereof, and belongs to the field of thermal protection of hypersonic aircraft. The method comprises the following steps: weighing alumina powder, mullite fiber powder, carbon fiber powder, sintering aid, deionized water, and dispersant in proportion, mixing and stirring evenly, and then ball milling and dispersing to obtain ceramic slurry; after the slurry is fully dried, grinding it into fine powder and sieving it; molding the fine powder and demolding it to obtain a material blank; after surface treatment of the thermocouple, processing small holes on the blank, implanting the thermocouple, filling the gap with ceramic fine powder, and using a pressure head to mold the fine powder in the gap to complete the in-situ implantation of the thermocouple; sintering in two steps under air environment and atmosphere protection conditions to obtain the material. The density of the material prepared in this application is 1.42~2.36 g / cm 3 , porosity 30%~60%, water permeability 10 ‑14 ~10 ‑13 m 2 The temperature resistance is ≥1500℃. It can meet the intelligent sweating cooling needs of high heat flow areas such as stagnation points and leading edges of hypersonic aircraft.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramic-based composite materials, and in particular relates to an in-situ implanted thermocouple ceramic-based sweating cooling medium material and a preparation method thereof. Background Art

[0002] In-situ thermocouple implantation: Before the sintering preparation of ceramic-based sweating cooling medium material components or parts is completed, the thermocouple wire temperature measuring element is implanted in advance and sintered in-situ inside the ceramic. The implanted thermocouple wire can measure the temperature on the surface or inside of the material.

[0003] Transpiration cooling: A cooling method in which the cooling medium (gas or liquid) flows from the cold end through the porous medium to the surface of the material, reducing the heat flow and temperature on the surface of the material through the phase change, heat capacity absorption and thermal blocking effect of the coolant.

[0004] Ceramic-based sweating cooling medium material: a ceramic-based composite material with uniform interconnected pores, which can allow the cooling medium to infiltrate from the inside of the porous ceramic material to the surface of the material under driving pressure.

[0005] The speed of near-space hypersonic vehicles is getting faster and faster. When flying at a high Mach number of more than 10 Ma, the total temperature of the gas at the stagnation point or leading edge will be as high as 4000K or more. For engines operating at a cruise Mach number of about 6, the total temperature of the internal airflow can reach more than 3000K. Traditional thermal protection solutions are mainly achieved by passive thermal protection means such as resin-based composite materials, carbon-based composite materials and ultra-high temperature ceramics, which can no longer meet the thermal protection needs of future hypersonic vehicles. The active thermal protection method of sweat cooling is one of the new heat reduction and drag reduction technologies. Due to its high cooling efficiency and other characteristics, it is considered to be the most promising technical means to solve the thermal barrier problem of future hypersonic vehicles. A lot of research has been conducted in this regard at home and abroad.

[0006] The sweating cooling medium material is the carrier of coolant flow and heat exchange. Its pore structure, permeability and mechanical strength are the key to the reliability of the sweating cooling system. At present, the main sweating cooling medium materials are porous metal materials such as stainless steel, bronze, brass, 3D printed high entropy alloys, etc. These traditional materials can be used for active thermal protection, but the disadvantages of porous metal materials such as stainless steel, bronze, brass are poor high temperature resistance (<1300℃) and high density (>4g / cm 3 ), there are problems of uneven pores and disconnection; the pores of 3D printed high entropy alloy porous materials are straight through holes, but the pore size is large (>10μm), and the sweating cooling efficiency is not high; porous ceramic materials have good high temperature resistance, and alumina porous ceramics can be used at a temperature above 1500℃ for a long time, with a small density (<2.5g / cm 3), can maintain the aerodynamic shape unchanged without ablation under limited sweating volume, and is more suitable for the sweating cooling application environment of hypersonic aircraft.

[0007] When the aircraft speed suddenly increases during flight and the heat flux on the material surface suddenly increases, sufficient coolant needs to be supplied in time. When the aircraft flies at a low Mach number, the amount of sweating needs to be reduced to prevent coolant redundancy, which is smart sweating. The premise of smart sweating is that the system can monitor the material temperature in real time through temperature sensors. Only by ensuring real-time feedback of the internal and surface temperatures of the material can the amount of sweating be accurately controlled to meet the requirements of the aircraft reliability and lightweight design for the smart sweating cooling system. Non-contact temperature measurement methods such as infrared temperature measurement are not applicable in flight environments. Therefore, thermocouples must be implanted in the dielectric material to collect temperature signals through thermocouples and transmit them to the intelligent control system in real time.

[0008] The common method of thermocouple implantation now is to drill holes to install thermocouples after the material is formed, use protective sleeves for insulation, and seal it by filling sealants and other measures. This causes the pore structure of the material to change after implantation. The protective sleeve and other devices affect the coolant seepage inside the material. In addition, ceramic materials are not easy to process. During the processing, local pores will be blocked, causing uneven surface sweating, easy heat transfer deterioration, and poor reliability. Before the ceramic is sintered, the thermocouple is implanted in the blank and sintered together. This is a way to solve various problems caused by later packaging. However, the ceramic sintering temperature is high and the sintering time is long. If no protective measures are taken for the thermocouple wire, it is easy to oxidize during the sintering process, resulting in the inability to measure temperature.

[0009] The Chinese public patent "A method for preparing ultra-high temperature ablation-resistant ceramic matrix composite material" prepared an ultra-high temperature ablation-resistant ceramic matrix composite material, but the material is a self-sweating cooling material that relies on the volatilization of Cu at high temperature. It is not as good as the cooling effect of the coolant actively sweating under driving pressure, and it cannot guarantee that the material will not be ablated and the surface will not retreat. Patent CN117226106A "Preparation method of gradient porous tungsten and gradient porous tungsten parts for sweating cooling" realizes a gradient porous structure based on binder injection molding technology; however, the pore connectivity is poor, the porosity is 10-50%, and the permeability is only 10 -15 ~10 -14 m 2The permeability is poor; Patent CN117403118A "A method for preparing a porous high-temperature resistant alloy material", the material in this invention has both the special functions of metal porous materials and the good high-temperature performance of refractory high-entropy alloys, but the metal material is not as good as the ceramic-based composite material in high-temperature resistance, and the temperature sensor is not implanted in situ, the material temperature collection feedback cannot be realized, and the sweating cooling control system cannot be connected for intelligent sweating. Patent CN117326046A "A thermal protection system capable of maintaining the shape of the surface of a hypersonic aircraft" discloses a porous ceramic body with a temperature sensor, the ceramic is porous alumina, porous mullite, porous silicon carbide, porous silicon nitride or porous zirconium oxide, the coolant penetrates through it to the aerodynamic heating surface, and heat reduction can be achieved, but the patent does not disclose the preparation method of porous alumina ceramics with temperature sensors and the material performance parameters of different ratios, and does not disclose the in-situ implantation process of thermocouples. Summary of the invention

[0010] The technical problem to be solved by the present invention is to provide an in-situ implanted thermocouple ceramic-based sweating cooling medium material and a preparation method thereof in view of the deficiencies of the prior art. The thermocouple is implanted in-situ during the material preparation process, and the prepared material has low density, high temperature resistance, and uniform and connected pore structure. The method uses alumina powder and mullite fiber as raw materials, carbon fiber as a pore-forming agent, and thermocouple wire as an implanted test element. The interconnected pores are formed by overlapping between fibers and particles and oxidation of the pore-forming agent. The uniformity of the pore structure is improved by grinding, and the mechanical strength of the porous material is improved by molding. The thermocouple and ceramic powder are sintered together by secondary molding of the blank, adding sintering aids, atmosphere protection, surface treatment of the thermocouple wire, and two-step sintering, and an in-situ implanted thermocouple ceramic-based sweating cooling medium material that can be used in an active thermal protection sweating cooling system is prepared. Thereby solving the problem that the existing sweating cooling materials have poor cooling effect and cannot realize the real-time temperature feedback function.

[0011] To achieve the above object, the technical solution adopted by the present invention is:

[0012] A method for preparing a ceramic-based sweating cooling medium material for in-situ implantation of thermocouples, the method comprising the following steps:

[0013] (1) Preparation of mullite fiber powder: ball-grinding and sieving mullite fiber loose cotton to obtain mullite fiber powder;

[0014] (2) Preparation of ceramic slurry: weigh alumina powder, mullite fiber powder obtained in step (1), carbon fiber powder, sintering aid, deionized water, and dispersant in proportion, add the dispersant into the deionized water, stir until completely dissolved, add alumina powder, mullite fiber powder, and carbon fiber powder in sequence, stir evenly, and disperse the mixed slurry by ball milling to obtain a uniformly mixed ceramic slurry; wherein, based on the weight of alumina, the amount of mullite fiber added is 40% to 75%, the amount of carbon fiber added is 25% to 75%, the amount of dispersant added is 0.5% to 2%, and the amount of sintering aid added is 2.5% to 5%;

[0015] (3) Drying and grinding: After the ceramic slurry obtained in step (2) is fully dried, it is ground into ceramic fine powder, and sieved to obtain fiber-reinforced alumina ceramic fine powder;

[0016] (4) blank forming: the fiber-reinforced alumina ceramic fine powder obtained in step (3) is molded and demolded to obtain a ceramic-based sweating cooling medium material blank;

[0017] (5) Thermocouple surface treatment: Add silicon carbide powder and dispersant to a solvent and disperse by ultrasonic to obtain silicon carbide slurry; spray the silicon carbide slurry evenly on the cleaned surface of the thermocouple wire, dry it thoroughly, and then sinter it under atmosphere protection for heat treatment;

[0018] (6) In-situ implantation of thermocouple: a small hole is processed on the blank prepared in step (4), the position and depth of the hole being determined by the temperature measuring point. After the thermocouple obtained in step (5) is implanted, the gap between the thermocouple and the blank is filled with the fiber-reinforced alumina ceramic fine powder prepared in step (3), and the fine powder in the gap is molded with a customized pressing head to complete the in-situ implantation of the thermocouple;

[0019] (7) Sintering: The material blank with the thermocouple implanted obtained in step (6) is sintered, first in an oxygen environment, then in an atmosphere for protection, the temperature is raised to the sintering temperature, the temperature is lowered according to a program after being kept at the temperature, and then the material is cooled with the furnace to obtain a ceramic-based sweating cooling medium material with an in-situ thermocouple implanted therein.

[0020] Furthermore, in step (2), the sintering aid is a TiO2-MnO2-MgO sintering aid, wherein the amount of TiO2 added to the sintering aid is 1%~2% of the weight of alumina, the amount of MnO2 added is 1%~2% of the weight of alumina; the amount of MgO added is 0.5%~1% of the weight of alumina; the dispersant is sodium carboxymethyl cellulose; and the solid phase content in the ceramic slurry is 15~25wt%.

[0021] Furthermore, in step (4) and step (6), the molding pressure is 50-100 MPa, and the pressure is maintained twice. The first time the pressure reaches 30%-40% of the set pressure, the pressure is maintained for 5 min-10 min, and the pressure is continued to reach the set pressure value, and the pressure is maintained for 10 min-15 min.

[0022] Furthermore, in step (5), the particle size of the silicon carbide powder is 3-8 µm, the solvent is xylene, the dispersant is superdispersant 7096, and the viscosity of the silicon carbide slurry is 1000-3000 mPa·s; the spraying thickness of the silicon carbide slurry is 100-200 µm; and the sintering heat treatment under atmosphere protection conditions refers to heat treatment at 1000°C-1300°C for 30 min-90 min in an atmosphere furnace under argon atmosphere protection conditions, with a heating rate of 3°C / min-10°C / min.

[0023] Specifically, in step (5), cleaning of the thermocouple wire refers to soaking the thermocouple wire in alcohol and then cleaning it in an ultrasonic cleaning machine. The ultrasonic cleaning temperature is 60-80° C. and the ultrasonic cleaning time is 60 min-120 min.

[0024] Furthermore, the step (6) of in-situ thermocouple implantation is as follows: first, the blank in step (4) is heat treated in a drying oven at 70-90°C for 10 h-15 h, then the blank is fixed with a fixture of the same size, a small hole with a diameter of 2 mm-3 mm is processed on the blank, and after the thermocouple wire is inserted, the fiber-reinforced alumina ceramic fine powder in step (3) is filled in the gap, and the fine powder in the gap is molded with a customized special-shaped pressing head to embed the thermocouple densely without destroying the blank structure, thereby completing the in-situ implantation of the thermocouple.

[0025] Furthermore, the sintering process in step (7) is as follows: under air conditions, the green blank is heated to 500°C~700°C at a rate of 1°C / min~3°C / min, kept at this temperature for 1h~3h, then the atmosphere furnace valve is closed, the gas passage is opened after vacuuming, argon gas is passed, and under inert gas protection, the temperature is raised to 1250°C~1550°C at a rate of 5°C / min~10°C / min, kept at this temperature for 2h~5h, cooled to 600°C~800°C at a rate of 3°C / min~5°C / min, and then cooled along with the furnace. When the temperature drops below 400°C, ventilation is stopped.

[0026] Furthermore, in step (2), the average diameter of the mullite fiber powder is 5-10 μm and the average length is 150-200 μm; the average particle size of the alumina powder is 1.0 μm-2.0 μm; and the average diameter of the carbon fiber powder is 5 μm-10 μm and the average length is 100 μm-150 μm.

[0027] Furthermore, in step (3), after grinding, the fiber-reinforced alumina ceramic fine powder is sieved through a 50-200 mesh sieve.

[0028] Furthermore, the thermocouple includes but is not limited to platinum-rhodium S type, platinum-rhodium B type, tungsten-rhenium 3 / 25 type, and tungsten-rhenium 5 / 26 type.

[0029] Preferably, in step (1), the ball-milled mullite fibers are sieved through a 50-200 mesh sieve.

[0030] In step (2), zirconium oxide balls are added during ball milling. The mass ratio of zirconium oxide balls of φ20 mm, φ10 mm, and φ5 mm is 5:3:2. The balls are dispersed for 200 min to 300 min. The ball mill speed is 200 to 300 r / min. The ball-to-material mass ratio is 2:1.

[0031] The in-situ implanted thermocouple ceramic-based sweating cooling medium material prepared by the preparation method.

[0032] The in-situ implanted thermocouple ceramic-based sweating cooling medium material of the present invention is mainly used for components or parts in high heat flow areas such as the stationary point, leading edge, rudder or rocket engine nozzle and combustion chamber wall of hypersonic aircraft that need to be cooled by sweating, and can be connected to a matching active thermal protection intelligent sweating cooling system.

[0033] The present invention has the following advantages:

[0034] (1) The present invention adopts a method of adding pore-forming carbon fiber and combining grinding-molding-sintering to prepare a ceramic-based sweating cooling medium material. By adjusting the raw material ratio and sintering process, the pores are evenly connected, the porosity is adjustable and controllable between 30% and 60% (some pores are formed by fiber overlap, and some are formed by carbon fiber pore formation), and the water permeability is between 10 -14 ~10 -13 m 2 It better meets the permeability performance requirements of the sweat cooling system for the dielectric material.

[0035] (2) The addition of different proportions of fibers in the sweating cooling medium material of the present invention plays a role in strengthening and toughening, and the room temperature compressive strength is increased to 40~130MPa, which increases the application range of ceramic-based porous medium materials.

[0036] (3) The present invention adopts an in-situ implantation design of thermocouples, which can be connected to a matching active thermal protection control system to realize intelligent sweating. The internal temperature of the material is tested in real time by the thermocouples, and the cooling system can control the sweating amount through the feedback temperature signal, thus solving the problem that the internal temperature data of traditional sweating cooling materials cannot be collected.

[0037] (4) The present invention treats the surface of the thermocouple and applies a protective coating to prevent the thermocouple wire from being oxidized during the sintering process with the porous ceramic. The thermocouple is densely buried without destroying the structure of the blank through secondary molding of the blank, adding sintering aids, atmosphere protection and two-step sintering. The failure of the thermocouple during the sintering process of the ceramic is prevented, and the pore structure and permeability of the sweating cooling medium material are not affected. The functional requirements of the intelligent sweating cooling system for real-time monitoring of the internal temperature of the key parts of the aircraft are met, ensuring that the control system can regulate the sweating amount in real time. The problems of decreased mechanical strength and uneven local sweating caused by the installation, fixation and sealing of the temperature sensor in the later stage are solved.

[0038] (5) The external dimensions and coolant passages of the material of the present invention can be flexibly designed, and the preparation method is simple and operable. The external dimensions and coolant passages can be reserved by designing the mold size. The material can be formed once before sintering, and does not require tedious subsequent machining processes. This avoids the problems of porous ceramic materials such as high hardness, difficult processing, and easy pore blockage. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a process flow chart of a method for preparing a ceramic-based sweating cooling medium material for in-situ implantation of thermocouples according to the present invention;

[0040] Figure 2 The pore size distribution diagram and electron microscope diagram of the in-situ implanted thermocouple ceramic-based sweating cooling medium material prepared in Example 1 of the present invention;

[0041] Figure 3 This is a physical picture of the in-situ implanted thermocouple ceramic-based sweating cooling medium material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below in conjunction with examples, but the protection scope of the present invention is not limited thereto.

[0043] The detection process of temperature resistance in the following embodiment is as follows: the surface of the sample is heated with an oxyacetylene flame, and the amount of sweating is controlled to maintain the surface temperature of the material at a set temperature of 1300°C-1600°C (close to the temperature resistance limit). After a 600s ablation test, the appearance, pore structure, and mechanical properties of the material do not change significantly, and the thermocouple temperature signal is stable without failure. The set temperature is the tolerance temperature of the sample.

[0044] Example 1

[0045] This embodiment includes the following steps:

[0046] Step 1. Preparation of mullite fiber powder: Take a certain amount of mullite fiber loose cotton according to the size of the ball mill, weigh three specifications of zirconium oxide balls of φ15mm: φ10mm: φ5mm=4:5:3 (weight ratio) according to the ball-to-material mass ratio of 10:1, ball mill at a speed of 300r / min for 12min in a planetary ball mill, sieve through an upper sieve of 50 mesh and a lower sieve of 200 mesh to obtain mullite fiber powder with an average diameter of 5-7μm and an average length of 180μm.

[0047] Step 2, preparation of ceramic slurry: solid content 20wt%, weigh alumina powder (α-Al2O3 powder, the same below), mullite fiber powder, carbon fiber powder according to the mass ratio of 4:3:3, weigh TiO2-MnO2-MgO sintering aid according to 4% of the weight of alumina (the addition amount of TiO2 is 2% of the weight of alumina, the addition amount of MnO2 is 1.5% of the weight of alumina, and the addition amount of MgO is 0.5% of the weight of alumina. The addition of sintering aids can reduce the sintering temperature and sintering time of alumina ceramics, reduce production costs, and improve production efficiency), and weigh sodium carboxymethyl cellulose as a dispersant according to 1.5% of the weight of the solid phase (adding an appropriate amount of sodium carboxymethyl cellulose can help α-Al2O3 particles and two fiber powders to be evenly dispersed in the liquid, thereby forming a stable suspension). The average particle size of alumina powder is 1.5μm, the mullite fiber powder is obtained in step 1, and the average diameter of carbon fiber powder is 7μm and the average length is 120μm. First, the dispersant was dissolved in deionized water, and stirred at 1200r / min for 30min with a disperser. Alumina powder, mullite fiber powder and carbon fiber powder were added in sequence, and stirred at 2500r / min for 90min. The mixed slurry was poured into a zirconia ball mill and dispersed for 240min. The ball-to-material mass ratio was 2:1. The weight ratio of three specifications of zirconia balls was φ20mm: φ10mm: φ5mm=5:3:2. The ball mill speed was 250r / min. After the ball milling was completed, the slurry was poured into a tin foil plate to obtain a well-mixed and well-dispersed ceramic slurry. Ball milling can prevent the fibers and powders from agglomerating or precipitating in the liquid through the collision and friction between the zirconia balls and the sample, and further improve the mixing uniformity of the raw materials.

[0048] Step 3, drying and grinding: the ceramic slurry obtained in step 2 is placed in a blast drying oven and fully dried for 24 hours, and ground into ceramic fine powder using an agate crucible, and the ceramic fine powder is sieved through an upper sieve of 50 mesh and a lower sieve of 200 mesh to obtain fiber-reinforced alumina ceramic fine powder.

[0049] Step 4, blank forming: the fiber reinforced alumina ceramic fine powder obtained in step 3 is loaded into the molding sleeve, the molding program is set using a universal testing machine, and the blank is pressed at room temperature and pressure. The pressure is controlled at a displacement speed of 1 mm / min. When the pressure reaches 15 MPa, the pressure is maintained for 2 minutes. The pressure is controlled at a displacement speed of 0.5 mm / min. When the pressure reaches 50 MPa, the pressure is maintained for 2 minutes (the segmented pressure maintenance is to ensure that the powder is evenly compacted during the pressurization process), and the ceramic-based sweating cooling medium material blank is obtained by demolding.

[0050] Step 5. Thermocouple surface treatment: Soak the thermocouple wire in alcohol and clean it in an ultrasonic cleaner at 70°C for 90 minutes. Add silicon carbide powder and dispersant Silok-7096 (purchased from Guangzhou Silok Chemical Co., Ltd.) into xylene and disperse it in an ultrasonic cleaner to obtain silicon carbide slurry with a viscosity of 2000mPa·s. Use an air spray gun to evenly spray the silicon carbide slurry on the surface of the thermocouple wire. The spray thickness of the silicon carbide slurry is 150µm (the silicon carbide coating can prevent the thermocouple from being oxidized during the sintering process and subsequent use in high-temperature environments). After sufficient drying, heat it to 1150°C at 5°C / min under argon protection and keep it warm for 1h.

[0051] Step 6. In-situ implantation of thermocouples: first heat treat the blank prepared in step 4 at 80°C in a drying oven for 12 hours, then fix the blank with a fixture of the same size, machine a 2-3 mm small hole on the blank, insert a platinum-rhodium B-type thermocouple wire, and fill the gap with the fiber-reinforced alumina ceramic fine powder prepared in step 3. Use a customized special-shaped indenter to mold the fine powder in the gap, and use the same conditions as step 4 to maintain pressure in two stages, so that the thermocouple is densely buried without destroying the blank structure, thereby completing the in-situ implantation of the thermocouple.

[0052] Step 7, sintering: sinter the material blank with the thermocouple implanted in step 5, first heat it to 500°C at 3°C / min in an air environment, keep it warm for 1h (carbon fiber powder is a pore-forming agent in the material system, and it is first heat-treated in an air environment to oxidize the carbon fiber powder and other organic matter in an oxygen environment to form carbon monoxide or carbon dioxide and other gases to overflow, so that the material forms interconnected pores), then close the atmosphere furnace valve, evacuate the air, open the gas passage, pass argon with a purity of 99.99%, and protect it with argon (atmosphere protection can prevent the thermocouple wire from being oxidized in a high temperature environment, and the gases used include but are not limited to argon and nitrogen) at 5°C / min to 1250°C, keep it warm for 4h, cool it down to 800°C at 3°C / min, and then cool it down with the furnace. When the temperature drops below 400°C, stop passing argon. The complete preparation flow chart is as follows Figure 1 As shown. The density is 1.44g / cm 3 , porosity 55.2%, water permeability 1.75×10-13 m 2 (The permeability of porous ceramics to water is obtained by testing according to GB / T 1969-1996 Test Method for Permeability of Porous Ceramics, the same below), the pore size is concentrated in the range of 5-11μm (such as Figure 2 The most probable pore size is 8 μm, and most pore sizes are distributed between 5 and 11 μm (as shown in the left figure). Figure 2 As shown in the right figure, a few pore sizes are distributed in the range of 0.2-5μm (such as Figure 2 As shown in the left picture), the in-situ implanted thermocouple ceramic-based sweating cooling medium material has a compressive strength of 40MPa and a temperature resistance of ≥1500℃. The actual picture is as follows Figure 3 shown.

[0053] Example 2

[0054] The difference between this embodiment and embodiment 1 is that the mass ratio of alumina powder, mullite fiber powder and carbon fiber powder in step 2 is 4:3:2, and the density of 1.61 g / cm is obtained in step 7. 3 , porosity is 42.4%, water permeability is 1.06×10 -13 m 2 , compressive strength 68MPa, temperature resistance ≥1500℃ in-situ implanted thermocouple ceramic-based sweating cooling medium material.

[0055] Example 3

[0056] The difference between this embodiment and embodiment 1 is that the mass ratio of alumina powder, mullite fiber powder and carbon fiber powder in step 2 is 4:3:1, and the density obtained in step 7 is 2.36 g / cm 3 , porosity is 35.9%, water permeability is 3.26×10 -14 m 2 , compressive strength of 130MPa, temperature resistance ≥1500℃, in-situ implanted thermocouple ceramic-based sweating cooling medium material.

[0057] Example 4

[0058] The difference between this embodiment and embodiment 1 is that the molding system described in step 4 is to pressurize at a displacement control speed of 1 mm / min, and maintain the pressure for 2 minutes when the pressure reaches 35 MPa, and to pressurize at a displacement control speed of 0.5 mm / min, and maintain the pressure for 2 minutes when the pressure reaches 100 MPa, and demold to obtain a ceramic-based sweating cooling medium material blank. In step 7, a density of 1.59 g / cm 3 , porosity is 49.8%, water permeability is 1.28×10 -13 m 2 , compressive strength 55MPa, temperature resistance ≥1500℃ in-situ implanted thermocouple ceramic-based sweating cooling medium material.

[0059] Example 5

[0060] The difference between this embodiment and embodiment 1 is that in step 5, the thermocouple wires are selected from platinum-rhodium S type, tungsten-rhenium 3 / 25 type or tungsten-rhenium 5 / 26 type.

[0061] Comparative Example 1

[0062] The difference between this comparative example and Example 1 is that no carbon fiber is added. That is, the mass ratio of alumina powder to mullite fiber is 4:3, and the prepared material is a relatively dense alumina ceramic with a density of >2.8 g / cm 3 , water permeability <1×10 -15 m 2 .

[0063] Comparative Example 2

[0064] The difference between this comparative example and Example 1 is that the thermocouple is not implanted in situ, and after the green billet is formed in step 4, the thermocouple is not implanted, and step 7 sintering is directly carried out to obtain the ceramic-based sweating cooling medium material. A small hole with a diameter of 2mm~3mm is processed in the material by a lathe, and the thermocouple is inserted and packaged. The compressive strength of the obtained material is less than 25MPa, and there is less sweating around the thermocouple.

[0065] By comparing Examples 1-4 with Comparative Example 1, it can be seen that the porous ceramics obtained in Examples 1-4 have a smaller density and a larger permeability, and can better meet the coolant seepage function requirements of the sweat cooling medium.

[0066] By comparing Examples 1-4 with Comparative Example 2, it can be seen that the porous ceramics obtained in Examples 1-4 have higher compressive strength, the in-situ implantation method avoids changes in the mechanical properties of the material caused by subsequent drilling and packaging, and the local sweating of the thermocouple embedded site is more uniform.

[0067] The above description is only a partial implementation mode of the present invention. For ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the principle of the present invention. These improvements and substitutions should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a ceramic-based sweating cooling medium material for in-situ implantation of thermocouples, characterized in that: The method comprises the following steps: (1) grinding and sieving the mullite fiber loose cotton to obtain mullite fiber powder; (2) Weigh alumina powder, mullite fiber powder obtained in step (1), carbon fiber powder, sintering aid, deionized water, and dispersant in proportion, add the dispersant into the deionized water, stir until completely dissolved, add alumina powder, mullite fiber powder, and carbon fiber powder in sequence, stir evenly, and disperse the mixed slurry by ball milling to obtain a uniformly mixed ceramic slurry; wherein, based on the weight of alumina, the amount of mullite fiber added is 40% to 75%, the amount of carbon fiber added is 25% to 75%, the amount of dispersant added is 0.5% to 2%, and the amount of sintering aid added is 2.5% to 5%; (3) After the ceramic slurry obtained in step (2) is fully dried, it is ground into ceramic fine powder, and sieved to obtain fiber-reinforced alumina ceramic fine powder; (4) molding the fiber-reinforced alumina ceramic fine powder obtained in step (3), and demolding to obtain a ceramic-based sweating cooling medium material blank; (5) Adding silicon carbide powder and dispersant to a solvent, and dispersing by ultrasonication to obtain silicon carbide slurry; spraying the silicon carbide slurry evenly on the surface of the cleaned thermocouple wire, and after sufficient drying, sintering and heat treatment under atmosphere protection; (6) machining a small hole on the blank in step (4), the position and depth of the hole being determined by the temperature measuring point, and after implanting the thermocouple obtained in step (5), filling the gap between the thermocouple and the blank with the fiber-reinforced alumina ceramic fine powder in step (3), and using a customized pressing head to mold the fine powder in the gap to complete the in-situ implantation of the thermocouple; (7) Sintering the material blank after the thermocouple is implanted obtained in step (6), first sintering in an oxygen environment, then passing the atmosphere for protection, heating to the sintering temperature, keeping the temperature and then cooling according to the program, and then cooling with the furnace to obtain a ceramic-based sweating cooling medium material with an in-situ thermocouple implanted.

2. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: In step (2), the sintering aid is a TiO2-MnO2-MgO sintering aid, wherein the amount of TiO2 added to the sintering aid is 1% to 2% of the weight of alumina, the amount of MnO2 added is 1% to 2% of the weight of alumina; the amount of MgO added is 0.5% to 1% of the weight of alumina; the dispersant is sodium carboxymethyl cellulose; and the solid phase content in the ceramic slurry is 15 to 25wt%.

3. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: In step (4) and step (6), the molding pressure is 50-100 MPa, and the pressure is maintained twice. The first pressure reaches 30%-40% of the set pressure and is maintained for 5 min-10 min. The pressure is continued to be pressed to the set pressure value and maintained for 10 min-15 min.

4. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: In step (5), the particle size of the silicon carbide powder is 3-8 µm, the solvent is xylene, the dispersant is superdispersant 7096, and the viscosity of the silicon carbide slurry is 1000-3000 mPa·s; the spraying thickness of the silicon carbide slurry is 100-200 µm; the sintering heat treatment under atmosphere protection refers to heat treatment at 1000°C-1300°C for 30min-90min in an atmosphere furnace under argon atmosphere protection, and the heating rate is 3°C / min-10°C / min.

5. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: The in-situ thermocouple implantation process in step (6) is as follows: first, heat treat the blank in step (4) in a drying oven at 70-90°C for 10 h-15 h, then fix the blank with a fixture of the same size, process a small hole with a diameter of 2 mm-3 mm on the blank, insert the thermocouple wire, fill the gap with the fiber-reinforced alumina ceramic fine powder in step (3), and use a customized special-shaped indenter to mold the fine powder in the gap so that the thermocouple is densely buried without destroying the blank structure, thereby completing the in-situ implantation of the thermocouple.

6. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: The sintering process in step (7) is as follows: under air conditions, the green blank is heated to 500°C~700°C at a rate of 1°C / min~3°C / min, kept at this temperature for 1h~3h, then the atmosphere furnace valve is closed, the gas passage is opened after vacuuming, argon gas is passed, and under inert gas protection, the temperature is raised to 1250°C~1550°C at a rate of 5°C / min~10°C / min, kept at this temperature for 2h~5h, cooled to 600°C~800°C at a rate of 3°C / min~5°C / min, and then cooled along with the furnace. When the temperature drops below 400°C, ventilation is stopped.

7. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: In step (2), the average diameter of the mullite fiber powder is 5-10 μm and the average length is 150-200 μm; the average particle size of the alumina powder is 1.0 μm-2.0 μm; and the average diameter of the carbon fiber powder is 5 μm-10 μm and the average length is 100 μm-150 μm.

8. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: In step (3), after grinding, the fiber-reinforced alumina ceramic fine powder is sieved through a 50-200 mesh sieve.

9. The method for preparing the in-situ implanted thermocouple ceramic-based sweating cooling medium material according to claim 1, characterized in that: The thermocouples include platinum-rhodium S type, platinum-rhodium B type, tungsten-rhenium 3 / 25 type, and tungsten-rhenium 5 / 26 type.

10. The in-situ implanted thermocouple ceramic-based sweating cooling medium material obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of gradient porous tungsten and gradient porous tungsten part for sweating and cooling

    CN117226106A

  • Thermal protection system capable of maintaining shape on surface of hypersonic aircraft

    CN117326046A

  • Method for producing high-strength shock resistant heat insulating porous ceramic

    CN101172882A

  • Molding method of mullite fiber reinforced magnesium silicate ceramic matrix composite material

    CN101838153A